CFD Study of Cuttings Transport through Vertical Wellbore - Al-Yasiri, Mortatha; Al-Gailani, Amthal; Wen, Dongsheng (Journal of Petroleum Research and Studies, 2018)
Cuttings transportation from the bit up the annulus to the surface is one the essential functions that are performed by drilling fluid. Predication of drilling fluid efficiency to transport cuttings in the annulus is very complicated due to numerous parameters that have affected drilling operations. Computational Fluid Dynamics (CFD) is widely used as a numerical technique in handling complex multiphase flow problems in different operational conditions. The present work has taken the advancement of CFD to computationally analyse the influence of the effects of various parameters like drilling fluid rheology, flow rate, pipe rotation, cuttings density, shape, concentration and drilling fluid- cuttings particle coupling regimes on the cuttings transport in a vertical wellbore. The CFD simulation was carried out by using transient solver of ANSYS-FLUENT CFD commercial code. The dense discrete phase model (DDPM) is suggested in this work to overcome the main shortcomings of Eulerian–Eulerian and CFD-DEM approaches in simulating drilling fluid-cuttings flow. Also, some of the experimental investigations were involved in determining the fluid physical properties and essential input data to perform the CFD simulations. Regarding the results validation and verification, well agreement has been achieved between results obtained in this study with those reported in other studies